Experimental Analysis of Air Inlet Height Variation in a Solar Tower system Using Plate and Metal Foam Absorber - Abdul Hussein, Sarmad A.; Nima, Mohammed A. (Al-Nahrain Journal for Engineering Sciences, 2022)
The experimental analysis is conducted under the Iraqi climate conditions to investigate the performance enhancement of a solar updraft tower system (SUTS) using the porous copper foam as an absorber plate and conventional absorber plate with absorber inclination angle of 18°. In the present work, a semicircular collector is divided into two identical quarter thermal collectors to become two identical SUTS. One of the quarter circular thermal collectors contains on the metal foam as an absorber plate, while the other quarter collector on the conventional flat copper absorber plate. In this study the air inlet height is changed of (3, 5, and 8) cm. The experimental tests carried out in Baghdad city (latitude 33.3° N). Results showed that the air inlet height variation caused to enhance the solar updraft tower performance. The highest values was recorded when the air inlet height is 3 cm using porous absorber compared to flat absorber plate. Copper material foam as an endothermic surface causes a marked decrease in average surface temperature of the plate. The maximum hourly thermal efficiency of solar collector was increased to about 41.6 % and the maximum enhancement of the power output to about 45.2 % compared with flat absorber plate.